Tinosporae Radix attenuates acute pharyngitis by regulating glycerophospholipid metabolism and inflammatory responses through PI3K-Akt signaling pathway - Lu, Lijie; Huang, Chengfeng; Zhou, Yongfeng; Jiang, Huajuan; Chen, Cuiping; Du, Jinyu; Zhou, Tao; Wen, Feiyan; Pei, Jin; Wu, Qinghua (Frontiers in Pharmacology, 2024)
➢ Integrated network pharmacology, metabolomics, and experimental validation have identified the pivotal pathway through which TR operates in the treatment of acute pharyngitis: the PI3K-Akt signaling pathway. ➢ By inhibiting the PI3K-Akt pathway, Tinosporae Radix suppresses the glycerophospholipid metabolism, thereby counteracting acute pharyngitis. ➢ Tinosporae Radix mitigates the inflammatory response associated with acute pharyngitis by inhibiting the release of inflammatory factors, such as IL-6 and TNF-α, as well as their mRNA expression, through modulation of the PI3K-Akt pathway. Abstract： Introduction: With the onset of the COVID-19 pandemic, the incidence and prevalence of acute pharyngitis (AP) have increased significantly. Tinosporae Radix (TR) is a vital medication utilized in the treatment of pharyngeal and laryngeal ailments, especially AP. The study endeavors to explore unclear molecular mechanisms of TR in addressing AP. Methods: Network pharmacology and metabolomics analyses of effect of TR on AP were conducted, and apossible pathway was validated both in vivo using the acute pharyngitis rat model and in vitro using the LPS-induced RAW264.7 cells model, through techniques such as histopathological examinations, immunohistochemical technology, ELISA, RT-qPCR, and Western blotting to systematically explore the possible mechanisms underlying the inhibition of AP by TR.Results and Discussion: Network pharmacology analysis identified several key targets, including PIK3CA, IL6, AKT1, TNF, and PTGS2, alongside pivotal signaling pathways such as IL-17, TNF, Hepatitis B, nuclear factor kappa B (NF-κB), Influenza A, and the PI3K-Akt pathway. Most of them are closely associated with inflammation. Then, wide-target metabolomics analysis showed that TR downregulated substances within the glycerophospholipid metabolic pathway, and modulated the PI3K-Akt pathway. The integrated findings from network pharmacology and metabolomics underscored the pivotal role of the PI3K-Akt signaling pathway and the attenuation of inflammatory responses. Finally, in vitro and in vivo experiments have shown that TR can inhibit inflammatory factors such as IL-6, TNF -α, and COX-2, downregulate targets such as PI3K and AKT on the PI3K-Akt signaling pathway, and thereby alleviate the inflammatory response of AP. Our study demonstrated that TR exerts an anti-AP effect through suppression of release of inflammatory factors and modulation of glycerophospholipid metabolism via suppressing the PI3K-Akt signaling pathway.